Analysis of Training Plans in Basketball: Gender and Formation Stage Differences - Cañadas, María (J Hum Kinet, 2018)
Scientific literature has stated the presence of various stages in athletes sportive development, with different objectives in each one of them. This should lead coaches to different training plans according to the athlete’s formation stage. The aim of this study was to analyse training plans and identify differences in basketball objectives according to formative stages (U’12 and U’14) in boys and girls. A total of 1,976 training tasks were collected and analysed, for a total of four teams (girls and boys of U’12 and U’14 categories) during an entire season. Pedagogical variables, game phases, game situations, training means and content were studied. The results showed significant differences between genders. Girls’ teams performed more tasks on offense and technical skills. By contrast, boys’ teams performed more defensive tasks and tactical contents. The 1-on-0 and 1-on-1 were the most repeated game situations in all teams. Coaches used different training tasks according to gender and age. In male U’12 teams, drills predominated, whereas in the other categories, games predominated. For boys’ teams, the contents were tactical oriented, and for girls’ teams, the contents were oriented toward skill acquisition. Studying the pedagogical variables of the training process allowed for identification of the utility of training, assessment, and modification of this process.